2011
DOI: 10.1128/aem.02895-10
|View full text |Cite
|
Sign up to set email alerts
|

Selective Quantification of Viable Escherichia coli Bacteria in Biosolids by Quantitative PCR with Propidium Monoazide Modification

Abstract: Quantitative differentiation of live cells in biosolids samples, without the use of culturing-based approaches, is highly critical from a public health risk perspective, as recent studies have shown significant regrowth and reactivation of indicator organisms. Persistence of DNA in the environment after cell death in the range of days to weeks limits the application of DNA-based approaches as a measure of live cell density. Using selective nucleic acid intercalating dyes like ethidium monoazide (EMA) and propi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 33 publications
3
69
0
1
Order By: Relevance
“…Enterobacteriaceae bacteria also serve as indicators of environmental pollution and can induce bacteremia (20). Thus, Enterobacteriaceae bacteria in milk have been targeted as a topic of broad concern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enterobacteriaceae bacteria also serve as indicators of environmental pollution and can induce bacteremia (20). Thus, Enterobacteriaceae bacteria in milk have been targeted as a topic of broad concern.…”
Section: Discussionmentioning
confidence: 99%
“…As a control compound for LD discrimination, 20 mM PMA (Biotium Inc., Hayward, CA, USA) was diluted in SW in the dark to concentrations of 100, 1,000, 2,500, 5,000, and 10,000 M. The diluted PMA solutions (10 l) were added to E. coli or C. sakazakii suspensions (generally, 90 l was used, with the exception that a 970-l suspension was used for milk samples) under a safelight. The bacterial suspensions were uniformly mixed, and the tubes were kept at 5°C for 10 min (typical treatment conditions) under a safelight, followed by visible-light irradiation (5 min) (19,20).…”
Section: Methodsmentioning
confidence: 99%
“…PMA treatment for this purpose has been shown to be effective in a range of contexts (Nocker et al, 2007a;Bae and Wuertz, 2009;Kralik et al, 2010;Nam et al, 2011;Taskin et al, 2011), including the assessment of microbiota present in CF airway samples (Rogers et al, 2008(Rogers et al, , 2010. Further, this strategy has been used previously in conjunction with bacterial pyrosequencing in waste-water treatment systems .…”
Section: Introductionmentioning
confidence: 99%
“…Morphologically damaged oocysts and cells have unprotected nucleic acid. Therefore, their amplification is restricted after EMA and PMA photo-activation (Nocker et al, 2006;Hein et al, 2007;Brescia et al, 2009;Chen and Chang, 2010;Byappanahalli et al, 2010;Taskin et al, 2011).…”
Section: Dye Based Viability Pcrmentioning
confidence: 99%
“…It has been demonstrated that Propidium Monoazide (PMA) (Biotium, Hayward, CA), a DNA intercalating dye, combined with PCR/qPCR methods can be used for selective detection/quantification of viable bacteria, protozoa and viruses from wastewater, sludge and environmental samples (Fittipaldi et al, 2011;Taskin et al, 2011;Nkuipou-Kenfack et al, 2013;Alonso et al, 2014;Li et al, 2014;Gensberger et al, 2014;Santiago et al, 2015). The working mechanism of PMA is that it penetrates non-viable cells or oo(cysts), and makes a covalent bond with DNA upon exposure to light preventing PCR amplification (Nocker et al, 2006;Nocker et al, 2007).…”
Section: General Introductionmentioning
confidence: 99%